Looking glass inhibitors: synthesis of a potent naringinase inhibitor L-DIM [1,4-dideoxy-1,4-imino-L-mannitol], the enantiomer of DIM [1,4-dideoxy-1,4-imino-D-mannitol] a potent alpha-D-mannosidase inhibitor - Hakansson, A; van Ameijde, J; Guglielmini, L; Horne, G; Nash, R; Evinson, E; Kato, A; Fleet, G (2007)
The synthesis of l-DIM [1,4-dideoxy-1,4-imino-l-mannitol] and of 1,4-imino-d-glycero-l-talo-heptitol from d-glycero-d-gulo-heptono-1,4-lactone depends on the use of pentan-3-one to form two five ring ketals as described by Burke, rather than the formation of one five ring and one six ring ketal formed with acetone. l-DIM, the enantiomer of the potent α-d-mannosidase inhibitor DIM [1,4-dideoxy-1,4-imino-d-mannitol] is a good inhibitor of naringinase (an α-l-rhamnosidase) with a K of 3.63 μM. 1,4-Imino-d-glycero-l-talo-heptitol is a moderate inhibitor of naringinase. © 2007 Elsevier Ltd. All rights reserved.